Mixed-methods evaluation of a behavioural intervention package to identify and amend incorrect penicillin allergy records in UK general practice - Sarah Tonkin-Crine; Robert West; Sinisa Savic; Jonathan Sandoe; Ly-Mee Yu; Sue Pavitt; Ushma Galal; Christopher C Butler; Marta Wanat; Bethany Shinkins; Mina Davoudianfar; Emily Bongard; et al. (BMJ Open)
Objectives About 6% of the UK general practice population has a record of a penicillin allergy but fewer than 10% of these are likely to be truly allergic. In the ALABAMA (Allergy Antibiotics and Microbial resistance) feasibility trial, primary care patients with penicillin allergy were randomised to penicillin allergy assessment pathway or usual care to assess the effect on health outcomes. A behavioural intervention package was developed to aid delabelling. This study aimed to investigate patients’ and clinicians’ views of penicillin allergy testing (PAT).Design We conducted a mixed-methods process evaluation embedded within the ALABAMA trial, which included a clinician survey, a patient survey (at baseline and follow-up) and semistructured interviews with patients and clinicians.Settings The study was conducted in primary care, as part of the feasibility stage of the ALABAMA trial.Participants Patients and primary care clinicians.Results Clinicians (N=53; 52.2%) were positive about PAT and its potential value but did not have previous experience of referring patients for a PAT and were unsure whether patients would take penicillin after a negative allergy test. Patients (N=36; 46%) were unsure whether they were severely allergic to penicillin and did not fear a severe allergic reaction to penicillin. Clinician interviews showed that they were already aware of the benefit of PAT. Interviews with patients suggested the importance of safety as patients valued having numerous opportunities to address their concerns about safety of the test.Conclusions This study highlights the positive effects of the ALABAMA behavioural intervention for both patients and clinicians.Trial registration number NCT04108637; ISRCTN20579216; Pre-results.